The effect of genitri (Elaeocarpus ganitrus) in leukocytes profile of wistar rats as a prospective immunomodulatory agent - Primiani, Cicilia Novi; Pujiati, Pujiati; Bhagawan, Weka Sidha; Waris, Waris; Krisnamurti, Gabriella Chandrakirana (Universitas Islam Negeri Sumatera Utara, 2025)
Immunomodulator is an agent to activate and modulate the immune response. It is one of the approaches to prevent chronic disease and maintain homeostasis. Recently, plant phytochemicals have been developed as prospective immunomodulatory agents. Genitri (Elaeocarpus ganitrus), a local plant cultivated in Indonesia, exhibited various biological properties and potential as an immunomodulatory agent. This study aims to identify the potency of genitri as immunomodulatory agent through leukocyte profiling. Genitri leaf (P1), seed (P2), and fruit (P3) were prepared as powder and administered to male wistar rats weighted 250-300 g twith six replications for 28 days. The total leukocytes were counted and leukocytes were being profiled following the treatment with genitri powder then compared with control treatment (P0). The immunomodulatory activity of genitri was shown by the increased leukocytes count following treatment. Based on data from the treatment group (P2), genitri seeds were able to increase leukocytes by 10595.83 cells/µl. The highest total leukocytes were found in treatment P2 with total leukocytes 10595.83 cells/µl. Based on the leukocyte profile, lymphocytes and monocytes were found to be the highest in all treatments. Treatment with genitri was able to stimulate an increase in lymphocytes and monocytes. An increase in total leukocytes given genitri is an indication of an increased immune response.